HPLC-ESI-HRMS2 Determination of N-(2-Hydroxyethyl)-l-valyl-l-leucine in Human Urine: Method Validation - Hanzlíková, Iveta; Mráz, Jaroslav; Tvrdíková, Monika; Chrástecká, Hana; Moulisová, Alena; Linhart, Igor (Journal of analytical toxicology, 2023)
Biomonitoring of human exposure to reactive electrophilic chemicals such as ethylene oxide (EO) has been commonly based on the determination of adducts with N-terminal valine in blood protein globin, but a systematic search has also been undertaken to find surrogate markers enabling non-invasive sampling. Recently, N-(2-hydroxyethyl)-L-valyl-L-leucine (HEVL) has been identified as an ultimate cleavage product of EO-adducted globin in the urine of occupationally exposed workers. Herein, full validation of the analytical procedure consisting of solid-phase extraction of HEVL from urine samples (2 mL) followed by high-performance liquid chromatography-electrospray ionization-high-resolution mass spectrometry determination using deuterium-labeled HEVL as an internal standard (IS) is described. Method limit of quantitation is 0.25 ng/mL, and its selectivity is excellent as demonstrated by the invariable ratio of the qualifier and quantifier ion intensities across diverse urine samples and synthetic standard. The linear calibration model was applicable over the whole concentration range tested (0.25-10 ng/mL). The method accuracy assessed as a recovery of HEVL using a spiking experiment was 98-100%. Within-day precision of the method ranged from 1.8% to 3.0%, while the results from consecutive analytical runs conducted within 1 week or within 10-150 weeks differed in the range of 2.2-9.7%. The stability study on urine samples (-20°C up to 3 years, freeze-and-thaw up to 10 cycles) as well as on aqueous solutions (5°C up to 4 months) indicated no relevant changes in HEVL concentration (≤4%) over the time tested. Analytical responses of both HEVL and IS correlated with urinary creatinine as an index of matrix composition, but this matrix effect was mostly eliminated using the HEVL/IS peak area ratio, attaining the IS-normalized relative matrix effect <3%. In conclusion, the method complied successfully with the bioanalytical method validation criteria, making it a reliable tool for HEVL determination in human biomonitoring.
Keywords: Dipeptides; Humans; Ethylene Oxide; ethylenoxid; Leucine; Chromatography, High Pressure Liquid; Reproducibility of Results; lidé; dipeptidy; reprodukovatelnost výsledků; vysokoúčinná kapalinová chromatografie; Globins; leucin; globiny